Lithuanian Mythological Creatures Laumės and their Equivalents in Russian and English - Gimževskienė, Karolina (Vertimo studijos, 2019)
This article aims to find cultural equivalents for the Lithuanian mythological creature laumė in the English and Russian languages. Therefore, a comparative analysis of similar mythological creatures in Lithuanian, Russian and English languages and cultures was carried out. The results of the analysis have shown which names of these creatures might be considered cultural equivalents. Such information is useful not only when choosing a domestication strategy, but for a foreignization strategy as well because these equivalents can be used both in the translation text itself and in additional extratextual comments. The conclusions given at the end of this article may be of practical importance for translators or authors writing about Lithuanian mythology and folklore for English or Russian speaking readers.